2022
DOI: 10.1111/jipb.13242
|View full text |Cite
|
Sign up to set email alerts
|

MALE STERILITY 3 encodes a plant homeodomain‐finger protein for male fertility in soybean

Abstract: Male-sterile plants are used in hybrid breeding to improve yield in soybean (Glycine max (L.) Merr.). Developing the capability to alter fertility under different environmental conditions could broaden germplasm resources and simplify hybrid production. However, molecular mechanisms potentially underlying such a system in soybean were unclear. Here, using positional cloning, we identified a gene, MALE STERILITY 3 (MS3), which encodes a nuclear-localized protein containing a plant homeodomain (PHD)-finger domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…According to the phenotypic characteristics, fs1fs2 (Johns and Palmer 1982) and ft (Singh and Jha 1978) belong to the structural MS, the others belong to sporogenous MS, and no functional MS has been reported in soybean. Although ve PGMS and TGMS lines have been identi ed, so far, only MS3 (Glyma.02G107600), encoding a plant homeodomain (PHD) protein, has been identi ed (Hou, et al 2022). The fertility of mutant ms3 can restore under long-day conditions, thus the mutant could be used to create a new, more stable photoperiod-sensitive genic male sterility line for two-line hybrid seed production in soybean.…”
Section: Gms System In Soybeanmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the phenotypic characteristics, fs1fs2 (Johns and Palmer 1982) and ft (Singh and Jha 1978) belong to the structural MS, the others belong to sporogenous MS, and no functional MS has been reported in soybean. Although ve PGMS and TGMS lines have been identi ed, so far, only MS3 (Glyma.02G107600), encoding a plant homeodomain (PHD) protein, has been identi ed (Hou, et al 2022). The fertility of mutant ms3 can restore under long-day conditions, thus the mutant could be used to create a new, more stable photoperiod-sensitive genic male sterility line for two-line hybrid seed production in soybean.…”
Section: Gms System In Soybeanmentioning
confidence: 99%
“…In soybean, the nuclear male sterile mutants ms4, ms1, ms6 and ms3 have been cloned in the recent years (Thu, et al 2019;Fang, et al 2021;Jiang, et al 2021;Nadeem, et al 2021;Hou, et al 2022). To speed up the large-scale commercial cultivation of hybrid soybean, it is time to consider where to put the investments, should we continue to count on the three-line hybrid system and looking for the ideal maintainer and restorer lines, or we can rely on the BMS systems to realize the commercialization of hybrid soybean.…”
Section: Introductionmentioning
confidence: 99%
“…Many transcription factors have been identified as being involved in thermosensitive genic male sterility in several crop species and Arabidopsis (Hou et al, 2022; Millar & Gubler, 2005; Wilson et al, 2010; L. Wu et al, 2022). Several appear to be conserved across plant species.…”
Section: Molecular Mechanism Regulating Thermosensitive Genic Male St...mentioning
confidence: 99%
“…The ms1 mutant in Arabidopsis also exhibits male sterility (Vizcay‐Barrena & Wilson, 2006). Interestingly, a knockout mutation of soybean MS3 , an ortholog of TMS9‐1 of rice and MS1 of Arabidopsis , resulted in photoperiod‐sensitive genic male sterility, and RNA‐seq analysis suggested that it may regulate carbohydrate metabolism (Hou et al, 2022). Overexpression of the wheat homologous gene MALE STERILITY1 ( HvMS1 ) shows reverse thermosensitive genic male sterility trait (Fernández‐Gómez et al, 2020).…”
Section: Molecular Mechanism Regulating Thermosensitive Genic Male St...mentioning
confidence: 99%
“…GMS is another important option due to its advantages of stable male sterility and extensive availability of fertility restoration sources. Especially in recent years, inspired by successful construction of the ‘third‐generation’ hybrid breeding systems in rice (Chang et al., 2016; Wang & Deng, 2018), mining of male sterility genes is not only meaningful for pollen developmental biology, but also becoming increasingly important and promising for hybrid seed production in crops such as wheat (Ni et al., 2017; Wang et al., 2017; Xia et al., 2017), soybean (Hou et al., 2022) and tomato (Du et al., 2020).…”
Section: Introductionmentioning
confidence: 99%